Review on Building Energy Performance - Jummai Shamang, Kasham (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Today, fossil fuels account for 44% of the world’s energy production, endangering both human health and the natural world. The construction industry is one of the major energy users, with a significant amount of the energy used being regarded as superfluous, according to a recent analysis of global needs for energy usage within different energy usage sectors. This is a result of inadequate management techniques and the use of preventative measures against excessive energy use. To address needless use of energy and guarantee optimal living conditions for sustainable urban areas, research in both academia and industry has concentrated on several strategies over time. This study presents a review of existing literature on building energy efficiency. The study extensively discussed energy performance, building data acquisition, and strategies for twin-building energy simulation. The study further identifies strengths and weaknesses in each aspect of the building energy performance discussed.